EKSISTENSI GURU DALAM PENANAMAN NILAI PENDIDIKAN ISLAM MULTIKULTURAL DI ERA MILENIAL - Ali Akbarjono (Institut Agama Islam Negeri Bengkulu, 2018)
The existence of Teachers at schools is important inimplementing the values of inclusive diversity in today's modern worldand plays a vital role in educating the values of social politeness, toleranceand mutual respect for generation z in this milineal era. The teacher hasan important role in multicultural education because he is one of thetargets of the education strategy in the literature on understandinghumanist, dialogical-persuasive, contextual, substantive and sociallyactive. Paradigm about the urgency of teachers to teach and implement thevalues of diversity in schools, teachers have an important role in fosteringstudents' social care attitudes, among others; (a) A teacher should havesufficient insight that multicultural Islamic education is essentiallyeducation that places multiculturalism as one of the visions of educationwith the main characters who are inclusive, egalitarian and humanist, butstill firm in spiritual and divine values based on al Qur'an and Sunnah;(b) Teachers should have sensitivity to discrimination and social, economicand political key justice that is happening; (c) The teacher must directlyapply the anti-discriminatory, social, political and economic attitudes inthe classroom; (d) The teacher does not discriminate between the students'children, officials and students of pedicab drivers, all are treated equally.